Egg rejection based on egg size recognition as a specific strategy against parasitic cuckoos. Issue 2 (14th May 2022) - Ye, Ping; Cai, Yan; Wu, Neng; Yao, Xiaogang; Li, Guangrong; Liang, Wei; Yang, Canchao
Abstract: In the coevolutionary interactions between avian brood parasites and their hosts, egg recognition based on color and/or pattern is a common and effective defense to counter parasitism. However, for egg recognition based on size, only a few studies have found affirmative results, and they do not provide unambiguous evidence that egg size recognition in hosts has evolved as an important and specific anti-parasite adaptation against parasite eggs. We studied the brood parasite system between the Asian emerald cuckoo Chrysococcyx maculatus and its host, the chestnut-crowned warbler Phylloscopus castaniceps . The cuckoo parasitizes the warbler using non-mimetic and larger eggs at a parasitism rate of 12.9%. The warbler nests used in this experiment were built in a dark environment with the nest illuminance near 0 lux. Experiments with 2 types of model eggs with colors and patterns resembling cuckoo eggs of different sizes (cuckoo egg size or host egg size) showed that the warblers were able to reject 63.6% of cuckoo model eggs under these dim light conditions. However, model eggs with the same color and pattern similar to the warbler egg size were always accepted. This study provides strong evidence supporting the theory that egg size recognition can be evolved in hosts as a specific anti-parasite adaptation against cuckoos. We suggest that the egg size recognition of the warbler is an outcome of the tradeoff between the costs of violating the parental investment rule and suffering cuckoo parasitism.